2020
DOI: 10.1016/j.fcr.2020.107779
|View full text |Cite
|
Sign up to set email alerts
|

Management options for reducing maize yield gaps in contrasting sowing dates

Abstract: Optimizing grain production implies defining the best management practices for a set of particular environments. Argentinean farmers in the central temperate region are sowing maize at two contrasting sowing dates (September to October and December), exposing their crops to very different growing environments. We tested the influence of management and environmental variables affecting maize yield at early (ES) or late (LS) sowings. Our objectives were to (i) determine the most relevant management and environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
2
11
1
Order By: Relevance
“…This rise impacted crop water availability, adding, in some cases, >300 mm of water (i.e., half of maize water requirements) (Portela et al, 2009) and helping achieve high and more stable yields when water table fluctuates around optimum levels (1.4-2.45 m depth; Nosetto et al, 2009;Rizzo et al, 2018). However, local studies also showed that shallow groundwater levels can have negative effects on maize yields under high rainfall levels (Vitantonio-Mazzini et al, 2020), especially when soil water tables are <1.4 m depth from soil surface, causing roots and plant death, salinization, and N loses (Nosetto et al, 2009;. Maize yield response to N rate depends on attainable yield and on the intrinsic capacity of the soil to deliver N (Salvagiotti et al, 2011).…”
Section: Crop Sciencementioning
confidence: 99%
“…This rise impacted crop water availability, adding, in some cases, >300 mm of water (i.e., half of maize water requirements) (Portela et al, 2009) and helping achieve high and more stable yields when water table fluctuates around optimum levels (1.4-2.45 m depth; Nosetto et al, 2009;Rizzo et al, 2018). However, local studies also showed that shallow groundwater levels can have negative effects on maize yields under high rainfall levels (Vitantonio-Mazzini et al, 2020), especially when soil water tables are <1.4 m depth from soil surface, causing roots and plant death, salinization, and N loses (Nosetto et al, 2009;. Maize yield response to N rate depends on attainable yield and on the intrinsic capacity of the soil to deliver N (Salvagiotti et al, 2011).…”
Section: Crop Sciencementioning
confidence: 99%
“…Data were analyzed using linear mixed-effects models to assess the influence of different predictors on grain yield (lme4 package, lmer function; Bates, Maechler, Bolker, & Walker, 2015). We applied the top-down strategy for the model selection process (Coyos et al, 2018;Gambin et al, 2016;Vitantonio-Mazzini et al, 2020;Zuur et al, 2009). After data exploration, we proposed a 'beyond-optimal model' which included different variables that presented association with grain yield.…”
Section: Statistical Analysis and Model Selectionmentioning
confidence: 99%
“…To explore the impact of multiple and potentially interactive management and environmental variables on soybean grain yield across the central Argentinean temperate region, we conducted 53 field trials in farmer fields during three consecutive cropping years. We used linear mixed‐effects models and multi‐model inference (MMI) techniques (Burnham & Anderson, 2004; Smith, Cullis, & Thompson, 2005) as they proved to be particularly useful to quantify multiple variable effects from experimental agricultural data (Casali, Rubio, & Herrera, 2018; Gambin, Coyos, Di Mauro, Borrás, & Garibaldi, 2016; Vitantonio‐Mazzini et al., 2020). We hypothesized that the most relevant management variables are sowing date and genotype selection, while water table presence and rainfall during the crop cycle are the most important environmental controls.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation models have been employed to demonstrate the negative effects of high temperature on spring wheat productivity in the cool regions (Xiao et al, 2017; Zhao et al, 2017). However, simulating sometimes is prone to errors and results always have a level of uncertainty (Vitantonio‐Mazzini et al, 2020). Inversely, other studies have shown that increased temperature in these regions improved wheat yield (He et al, 2020; Xiao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%